Effective oversight roles of board of directors - the case of listed firms on Bursa Malaysia - Mohd Saat, Nur Ashikin (2011)
This study investigates the influence of strong committee of independent directors on the board of directors on firm value. We focus on the factors that strengthen independent directors’ performance of fiduciary duties notably the presence of independent financial expert, senior independent director, independent board’s chairman, and absence of top management executives and presence of family members on the board of directors. We conduct our research using 221 samples of Malaysian listed companies. This study extends prior research by emphasizing the significance of regulating the appointment of independent financial expert and the support of independent director with in depth corporate governance experience on the board. The results show that board oversight roles enhanced firm performance when a senior independent director and an independent board’s chairman were present on the board where CEO, CFO, COO or MD was not a board member. Furthermore, the negative relationship between the proportion of family member director on the board and firm performance supported the imperativeness of higher independent director presence on the board. These findings provide empirical evidence in support of the significance of board independence as an effective governing mechanism for monitoring family-member director influence on board decisions. On the other hand, the negative relationship between the presence of more than majority independent director on the board and firm performance signifies their productivity is valued more than numbers.